2019
DOI: 10.1001/jamadermatol.2019.2346
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Excisional Surgery Practices for Melanoma in the United States

Abstract: guidelines for melanoma have consistently recommended wide local excision as the standard of care since their inception. Although surgery with more comprehensive margin assessment (eg, Mohs surgery) has been advocated for certain subsets of melanoma, how often these techniques are used in clinical practice is uncertain. OBJECTIVE To examine trends in the use of comprehensive margin assessment surgery for melanoma by tracking claims data for Mohs surgery. DESIGN, SETTING, AND PARTICIPANTS This national cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Previous studies have described wide variation in use rates and practice patterns amongst Mohs surgeons, prompting the American College of Mohs Surgery to develop appropriate use criteria (AUC) for MMS in 2012. [9][10][11] Yet, the results of this study suggest that the use rate of MMS continued to increase despite the adoption of AUC. However, numerous factors beyond economic incentives may have also contributed to this trend.…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies have described wide variation in use rates and practice patterns amongst Mohs surgeons, prompting the American College of Mohs Surgery to develop appropriate use criteria (AUC) for MMS in 2012. [9][10][11] Yet, the results of this study suggest that the use rate of MMS continued to increase despite the adoption of AUC. However, numerous factors beyond economic incentives may have also contributed to this trend.…”
Section: Resultsmentioning
confidence: 68%
“…This risk is mitigated by taking an incisional biopsy from the most atypical appearing area of the tumor at the first stage of excision to check for any invasive component. The use of Mohs surgery with immunostains, which is increasingly used for melanoma in the United States, 39 could help to avoid these drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…13,22 A recent survey of Mohs surgeons and database analysis suggests wide-spread use of MART-1 in MMS for CM. 23,24 With techniques in MMS for treating melanocytic lesions evolving, there is an impetus to continue to evaluate emerging research for further clinical guideline development. To date, no systematic reviews have specifically examined the utilization of MART-1 staining in frozen sections for CMparticularly its effect on local recurrence.…”
Section: In-depth Review Melanoma Recurrence After Mohs Micrographic Surgery With Mart-1: a Systematic Review And Meta-analysismentioning
confidence: 99%
“…Twenty-seven percent of the MMS cases reported use of Immunohistochemistry stains (IHC), with an increase in utilization over recent years with further acceptance of its benefit. 24 In addition to ease of use/interpretability and outcome improvement, it is important to investigate financial feasibility. Wilson et al demonstrated that among comprehensive margin assessment techniques for MIS/IM, staged excision using en-face margin assessment (SEEM) and MMS with MART-1 were similar in cost for the healthcare system.…”
Section: Risk Of Biasmentioning
confidence: 99%